Use of polyclonal rabbit antibodies for detection of the bcr-abl fusion zone in cells transfected with experimental bcr-abl DNA vaccines - Ludvíková, V; Hamsíková, E; Sobotková, E; Lucansky, V; Smahel, M; Vonka, V (International journal of oncology, 2005)
Rabbits were immunized with peptides covering the fusion zone of the chimeric bcr-abl protein in order to prepare antibodies capable of detecting the expression of a selected portion of this fusion zone, by a variety of experimental genetic vaccines. Three peptides of different size covering the b3a2 fusion zone, either unmodified or modified by the omission of alanine at the N-terminal of the a2 section of the fusion zone, and one peptide covering the unmodified b2a2 fusion zone were used. All were capable of eliciting antibodies reactive with the respective immunizing peptides. Their cross-reactivities, especially the results of cross-absorption experiments, strongly suggested that the serum of the rabbit immunized with an octadekapeptide mimicking the b3a2 fusion zone contained antibodies against a novel antigenic determinant created by the chimeric protein, and also against an epitope present in the adjacent a2 section but no antibody reactive with the adjacent b3 region. In Western blotting, these antibodies were capable of detecting the p210bcr-abl or a portion of it (a 25 amino acid-long sequence covering the b3a2 fusion zone) in lysates of 293T cells transfected with plasmids that carried either the full cDNA of the bcr-abl gene or a fragment thereof fused with either the HSP70 gene or certain other genes.
Keywords: Models, Genetic; bcr-abl fúzní proteiny; Protein Structure, Tertiary; nádorové buněčné linie; modely genetické; Mice, Inbred BALB C; Vaccines, DNA; DNA, Complementary; Antibodies; protilátky; transfekce; Fusion Proteins, bcr-abl; HSP70 Heat-Shock Proteins; Mice; Cell Line, Tumor; western blotting; Peptides; Blotting, Western; komplementární DNA; zvířata; Humans; králíci; Plasmids; Rabbits; myši inbrední BALB C; Transfection; myši; peptidy; plazmidy; proteiny tepelného šoku HSP70; DNA vakcíny; terciární struktura proteinů; lidé; Animals